CONSUMER PREFERENCE FOR ALTERNATIVE MILK PACKAGING: THE CASE OF AN INFERRED ENVIRONMENTAL ATTRIBUTE. (13th September 2016) - NEILL, CLINTON L.; WILLIAMS, RYAN B.
Abstract: Ecolabeling allows firms to segment a market by informing consumers about unobservable attributes of a product. Previous studies evaluate consumer preferences for products explicitly labeled as possessing positive environmental attributes. This research evaluates consumers' willingness to pay for a product that is perceived by the consumer as having environmentally friendly attributes. We explore glass packaging for fluid milk as a case study. Data were collected through a contingent valuation survey, and a bound-and-a-half logit model was employed. The estimated premium is 59.78 cents with a premium between 0.73 and 0.92 for consumers more likely to prefer the glass alternative.